2008
DOI: 10.2528/pierb08031221
|View full text |Cite
|
Sign up to set email alerts
|

Analytical and Numerical Aspects of Bragg Fiber Design

Abstract: Abstract-Analytical theory and numerical approaches to the simulation and optimal design of multilayer mirrors and optical Bragg waveguides are developed. Optimal refractive index profiles in planar and cylindrical geometry are found. Reduction of the full set of Maxwell's equations to a scalar boundary value problem in the lowcontrast approximation is discussed. An efficient finite-difference scheme is used to simulate realistic Bragg fibers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…where G 11 , G 12 , G 21 and G 22 are submatrices of either G PUA in (17) or G RKM in (24). Assume that core mode is incident from z = 0, and no reflection wave exists at z = L. A(L), the transmission amplitude vector at z = L and B(0), the reflection amplitude vector at z = 0 can be expressed as…”
Section: Runge-kutta Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…where G 11 , G 12 , G 21 and G 22 are submatrices of either G PUA in (17) or G RKM in (24). Assume that core mode is incident from z = 0, and no reflection wave exists at z = L. A(L), the transmission amplitude vector at z = L and B(0), the reflection amplitude vector at z = 0 can be expressed as…”
Section: Runge-kutta Methodsmentioning
confidence: 99%
“…Since the structure of apodized FBGs is more complicated than that of uniform FBGs, there are many methods presented to explore the performance of apodized FBGs [14][15][16][17]. In this paper, we use CMT to analyze apodized FBGs.…”
Section: Introductionmentioning
confidence: 99%
“…More recently Bragg waveguides having unconventional structure and geometry [17,18] have been studied by Prajapati et al using this simple technique. Very recently the analytical and numerical aspects of Bragg fiber designing was estimated by Prokovich et al [19]. Here in our proposed paper we will study a new asymmetrical Bragg Waveguide having six layers shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…We demonstrate that when an appropriate detection method is used, within a wide current range, the measurement can be made independent of the position of the conductor surrounded by the core. In Section 4, we develop an analytical model for the considered sensor, which enables computationally efficient simulations to be carried out [7]. This model is implemented using a time-discretization method so as to determine the non linear dynamic response of the sensor.…”
Section: Introductionmentioning
confidence: 99%